2024
DOI: 10.1088/1361-6560/ad3c0a
|View full text |Cite
|
Sign up to set email alerts
|

b-MAR: bidirectional artifact representations learning framework for metal artifact reduction in dental CBCT

Yuyan Song,
Tianyi Yao,
Shengwang Peng
et al.

Abstract: Objective. Metal artifacts in computed tomography (CT) images hinder diagnosis and treatment significantly. Specifically, dental cone-beam computed tomography (Dental CBCT) images are seriously contaminated by metal artifacts due to the widespread use of low tube voltages and the presence of various high-attenuation materials in dental structures. Existing supervised metal artifact reduction (MAR) methods mainly learn the mapping of artifact-affected images to clean images, while ignoring the modeling of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(37 reference statements)
0
0
0
Order By: Relevance
“…A recent study by Park et al [ 41 ] showed that DL methods, such as fidelity-embedded learning, significantly reduce metal artifacts while preserving morphological structures near metallic objects in dental CBCT. In a recent article from 2024, Song et al [ 42 ] proposed a bidirectional artifact representation learning framework to adaptively encode metal artifacts. The authors proved that their method showed superior performance over existing methods in restoring the structural integrity of dental tissues and removing artifacts effectively.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Park et al [ 41 ] showed that DL methods, such as fidelity-embedded learning, significantly reduce metal artifacts while preserving morphological structures near metallic objects in dental CBCT. In a recent article from 2024, Song et al [ 42 ] proposed a bidirectional artifact representation learning framework to adaptively encode metal artifacts. The authors proved that their method showed superior performance over existing methods in restoring the structural integrity of dental tissues and removing artifacts effectively.…”
Section: Discussionmentioning
confidence: 99%